(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2019)
There are dual roles of higher education institutions as recipients of higher education policy and as agents for change in the knowledge economy in their regions and in the world. In the case of academic institutions within the European Union, they are primarily the recipients of policy change influenced by the European level. Secondarily, they are agents of policy change in the knowledge-based economy, which is of increasing importance in the 21st century. This is a new kind of regional integration, influenced by Europeanization and intergovernmentalism in higher education policy, with the ultimate objectives for economic competitiveness and social cohesion attained by recognition of qualifications. The success of the European Commission’s study abroad program, Erasmus, is provided as background to the development of the Bologna Process, for which there have been mobility objectives in higher education. The opportunity for greater mobility in international education corresponds with ongoing trends in globalization.